UMPSA organises iNCLUSIVE 2025 to strengthen commitment towards inclusive technology and education - Naqiah, Puaad (UMPSA, 2025)
PEKAN, 29 May 2025 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) marked its milestone by organising for the first time the International Carnival on Inclusive Technology and Ecosystem (iNCLUSIVE) 2025, held at the UMPSA Library, Pekan.